A study on the economic, social, and personal factors influencing the decision of students to enroll in and continue with library and information science as an undergraduate course - Pasion, Dan Oliver C. (2011)
According to the enrollment data from the School of Library and Information Studies of the University of the Philippines from the 1st semester of SY 2007-2008 to 1st semester of SY 2010-2011, there was a decline of freshmen students and increase of shiftees and transferees who enrolled in the Library and Information Science course. This may be attributed to a variety of reasons, one of the most important of which is the School's admission requirements. However, the researcher believes that perceptions play a key role in the decision of students, especially those of university students who have already gained additional experiences in their few months or years of staying in the university. In other words, negative perceptions influence the decision of students not to enroll in an LIS course and positive perceptions gained through experiences influence the decision of students to enroll in, remain and complete the course.